Pengaruh Suku Bunga, Nilai Tukar Valas, dan Jumlah Uang Beredar Terhadap Profitabilitas Pada Perbankan Syariah - Ariefudin Ariefudin; Muhammad Agus Salim; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine and analyze the partial and simultaneous influence of interest rates, foreign exchange rates, and the money supply on profitability in Islamic public banks in Indonesia in 2014-2018. This research was conducted at the Financial Services Authority through the Unisma Investment Gallery with the number of samples used was 14 sharia general banking companies in Indonesia in the 2014-2018 period.            The data analysis technique uses multiple linear regression analysis. The analysis shows that interest rates partially have a significant negative effect on profitability (ROA). Foreign exchange rates have no significant positive effect on profitability (ROA). The money supply does not have a significant negative effect on profitability (ROA). Simultaneously, interest rates, foreign exchange rates, and the money supply affect the profitability (ROA) of Islamic sharia banks in Indonesia in 2014-2018.Keywords: interest rates, foreign exchange rates, money supply, profitability